Effectiveness of Malaysia football DNA application on the performance of players under 16 years - Hadi Syahmi Hamzah; Zulakbal Abd Karim; Abdul Rahaman; Fakrul Hazely Ismail; Amin Akbar (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: Malaysia launched the Malaysian Football DNA (F30) in 2018 to establish a standardized philosophy and playing style across all levels of football. This model, created by the Football Association of Malaysia (FAM), reflects the philosophy, culture, and unique characteristics of Malaysian football, aligning with the demands of modern gameplay.